Pengaruh Toxic Leadership, Project Team Member's Silence, dan Sustainable Project Management Terhadap Project Success Pada Karyawan di Lingkungan Pemerintah Pusat - Kanissa, Rininta Andriani; Kurniawan, Aziza Idris; Emilisa, Netania (Jurnal Ilmiah Wahana Pendidikan, 2023)
The aim of this study is to analyze the influence of Toxic Leadership, Project Team Member's Silence, and Sustainable Project Management on Project Success. This research using the purposive sampling with 246 employees working in the central government environment. The analysis method used was multiple regression analysis using SPSS software version 25. The research findings indicate that Toxic Leadership significantly has a negative influence on Project Success, while Project Team Member's Silence does not have an influence on Project Success. On the other hand, Sustainable Project Management significantly has a positive influence on Project Success. The implications for organizations within the central government environment through this research are expected to gain knowledge about the conditions experienced by employees during project implementation and pay attention to the factors that can affect the occurrence of Project Success, so that overall performance will be efficient and effective throughout the project and achieve the desired results.